A thermo-sensitive injectable hydroxypropyl chitin hydrogel for sustained salmon calcitonin release with enhanced osteogenesis and hypocalcemic effects. Issue 2 (5th December 2019) - Yu, Peng; Xie, Jing; Chen, Yu; Liu, Jinming; Liu, Yanpeng; Bi, Bo; Luo, Jun; Li, Sheyu; Jiang, Xulin; Li, Jianshu
Abstract : An injectable thermo-sensitive hydroxypropyl chitin hydrogel was applied for long-term sCT release, with enhanced osteogenic potential and hypocalcemic effects. Abstract : Pharmacotherapy towards hypercalcemia treatment mainly caused by osteoporosis and bone tumor is an effective method to regulate in vivo calcium equilibrium. As a clinical therapeutic peptide, salmon calcitonin (sCT) is considered as a quick-acting medicine but it is limited by the short half-life. To address this challenge, we designed an injectable thermo-sensitive hydrogel based on hydroxypropyl chitin (HPCH) and incorporated the complex of sCT and hyaluronic acid (HA) (sCT–HA) with high association efficiency up to 96.84 ± 7.25%. This composite hydrogel showed a tunable biodegradable property. In vitro sCT release profiles revealed that this hydrogel can achieve long-term sustained sCT release (28 days) with considerable structure stability. The cellular study illustrated outstanding compatibility and osteoconductive potential of this multi-component hydrogel according to the higher ALP activity (2.10-fold), calcium expression (2.30-fold) and extracellular calcium deposition (1.10-fold) compared to that of the sCT group. In vivo sCT release confirmed that this hydrogel system realized sustained sCT release and a continuous hypocalcemic effect for as long as 28 days, and there were no inflammation and immune responses according to the histological evaluations (H&E and IgG staining). These findings demonstrate that this osteoconductive hydrogel system can provide a promising method for therapy of bone related disease.